Naturally felt emotions, work engagement: the moderating role of perceived organizational support - Cinthia Annisa Vinahapsari; Hazril Izwar Ibrahim; Jeniboy Kimpah (Institute of Advanced Engineering and Science, 2024)
The main purpose of this study is to investigate whether or not emotional labor strategy (i.e., naturally felt emotions) significantly predicts work engagement (i.e., vigor, dedication, absorption) among academicians in a higher education setting. It also evaluates the role of perceived organizational support (POS) as the moderating variable between naturally felt emotions (NFE) and work engagement. This study employs a survey questionnaire, and data collected from private universities in Central Java, Indonesia. To analyze the data and test the proposed model, the partial least squares structural equation modelling approach was employed. The findings demonstrate that: i) NFE are significantly and positively related to all work engagement dimensions; and ii) POS is proven insignificant to moderate the relationship between NFE and work engagement dimensions. The results of this study complement the literature by addressing associations between NFE and work-related outcomes (i.e., work engagement), especially in the Indonesian academic context. In addition, this study also confirms the insignificant role of POS which is based on norms of mutuality between the organization and employee. Finally, the study offers recommendations and conclusions to achieve long-term objectives for higher education institutions.